Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/0961000618788726
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, perceptions and prospectings on mobile information literacy training: Design and validation of the MOBILE-APP questionnaire

Abstract: The basic aim of this paper is to outline the process of designing and validating an instrument for measuring teachers’ perceptions regarding the importance of using mobile technologies in the teaching-learning of information competencies (MOBILE-APP). Validation was carried out by administering the instrument to a pilot group of teachers, all of whom were experts in new technologies selected from the Information and Communication, Business and Education degrees, together with a rubric to analyse the quality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Furthermore, the present study reconfirms the point raised by Pint et al (2020) that there is a considerable shift in technological advancement, and thus in people's perspectives. People like to spend more time on social media rather than on reading books or journals.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the present study reconfirms the point raised by Pint et al (2020) that there is a considerable shift in technological advancement, and thus in people's perspectives. People like to spend more time on social media rather than on reading books or journals.…”
Section: Discussionsupporting
confidence: 88%
“…Pinto et al (2020) showed that of late, teachers have started to realize the importance of Internet tools such as Facebook, Instagram and emailbecause these tools are instrumental in promoting English language learning skills. Though the study was focused on Twitter and Instagram, it served as a guide for the future researchers and teachers to adopt these mediums for the language learning practices.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In this way, previous studies on mobile learning in higher education, focused on Spain, have been mainly dedicated to the analysis of the perceptions of teachers and students and the conditions for its adoption [29] [36] . This differs from the knowledge about the real application of mobile devices in the Spanish university context.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, it is worth noting that the MOBILE-APPS questionnaire was processed and created separately from the MOBILE-APP scale, which was designed for teachers (Pinto et al, 2018). In other words, these are two independent questionnaires.…”
Section: Discussionmentioning
confidence: 99%